Evaluation of the effect of non-enzymic antioxidant and trace element status in diabetes mellitus patients in Ile-Ife, Osun state, Nigeria. - Fagbohun, Oladapo Fisoye (Biochemistry, Obafemi Awolowo University, 2020)
xviii, 105p